Asas Strict Liability sebagai Instrumen Penegakan Hukum dalam Kasus Kebakaran Hutan dan Lahan Putusan Nomor 234/PDT.G/LH/2016/PN PLG - Zulkipli; Windi Arista; Luil Maknun (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
In terms of environmental protection, including in cases of forest and land fires, the principle of strict liability provides a strong legal basis for law enforcement against those who cause environmental damage without the need to prove that they acted with fault or malicious intent. This is important considering the ecological, social, and economic impacts caused by forest and land fires. Forests are very important for national and international life. About two-thirds of Indonesia's 191 million hectares of land is covered by forests with diverse ecosystems, ranging from lowland tropical forests and montane tropical forests to peat swamps, freshwater swamps, and mangrove forests. (mangrove). In cases of strict liability, the plaintiff only needs to prove the existence of harm and the causal relationship between the actions of the defendant and the legal efforts to prevent forest and land fires.